Comparative Risks of High-Grade Adverse Events Among FDA-Approved Systemic Therapies in Advanced Melanoma: Systematic Review and Network Meta-Analysis - Huang, Ya-fang; Xie, Wen-jie; Fan, Hai-yu; Du, Juan (Frontiers in Oncology, 2020)
Background: Head-to-head evidence is lacking in comparative risks of high-grade adverse events (AEs) among different systemic treatment options for advanced melanoma. Methods: An up-to-date systematic review and network meta-analysis (NMA) was performed. Randomized controlled trials (RCTs) of patients with advanced melanoma were eligible if at least one intervention was the FDA-approved targeted or immune checkpoint inhibitors (ICIs). Risks of high-grade AEs were estimated by random-effects Bayesian NMAs, based on relative risks (RRs). Surface under the cumulative ranking (SUCRA) probabilities was used to assess relative ranking of treatments. The summary incidences were calculated. Results: Twenty-five RCTs (12925 patients) comparing ten different systemic treatment options were included. BRAF/MEK had the highest risk of overall high-grade AEs (pooled incidence: 32.11%). BRAF had the highest risk of high-grade arthralgia (0.39%), whereas MEK had the highest risk of high-grade hypertension (2.28%) and nausea (0.37%). CTLA-4/Chemo had the highest risk of high-grade diarrhea (1.31%), ALT (0.60%) and AST elevation (0.59%). PD-1/CTLA-4 had the highest risks of high-grade pyrexia (1.14%) and rash (0.94%). Using PD-1 inhibitor alone had the lowest risks of overall high-grade AEs. Conclusions: Different systemic treatment options have varying high-grade AEs in advanced melanoma treatment. Current evidences highlight the important risks of BRAF/MEK, CTLA-4/Chemo and PD-1/CTLA-4.